A Comparison of the Incidences of Venous Thromboembolism after Total Hip Arthroplasty between the Direct Anterior Approach and the Direct Lateral Approach, Especially in the Early Period after Introduction of the Direct Anterior Approach. (4th June 2020) - Kawano, Tetsuya; Kijima, Hiroaki; Yamada, Shin; Konishi, Natsuo; Kubota, Hitoshi; Tazawa, Hiroshi; Tani, Takayuki; Suzuki, Norio; Kamo, Keiji; Okudera, Yoshihiko; Fujii, Masashi; Sasaki, Ken; et al.
Abstract : Objective . To compare the incidence of venous thromboembolism (VTE) after total hip arthroplasty (THA) using the direct anterior approach (DAA) with that using the direct lateral approach (DLA). In addition, patient background characteristics and the incidence of VTE were compared between the first half and the latter half of the period after introducing DAA and against DLA. Method . This was a retrospective, multicenter study involving 109 patients (116 hips) who had undergone primary unilateral THA. Thirty-six hips underwent THA using DAA and 80 hips underwent THA using DLA. Patient information including sex, age, and preoperative diagnosis was collected. The incidence of VTE was compared between DAA and DLA. Moreover, the patients who underwent THA using DAA were divided into 2 groups (first half and latter half groups), and sex, age, body mass index (BMI), and surgical time were compared between the 2 groups. Moreover, the incidence of VTE was compared among the 3 groups (first half of DAA, latter half of DAA, and DLA). Results . The incidence of VTE in the DAA group was significantly higher than that in the DLA group p = 0.014 . The incidence of VTE in the first half group was significantly higher than in the latter half group and the DLA group (p = 0.035 and p = 0.001, respectively), and there was no difference in the incidence of VTE between the latter half group and the DLA group p = 0.923 . Surgical time was significantly longer in the first half group than in the latter half group p = 0.046 . Conclusions . In the first half of the period after introducing the DAA, more VTEs occurred than in the DLA. It may be important to shorten the surgical time in the early stage of introducing the DAA, and aggressive anticoagulation therapy may be required until the surgeon becomes familiar with the procedure.